The Organoleptic Test For Tempe-Based Drink Formulation For The Prevention Of Cognitive Function In Elderly Women - Kridawati, Atik; Ulfa, Laila (Journal of Ageing And Family, 2023)
Older women are at twice the risk of developing Alzheimer's Disease than men. This happens because when women experience menopause, estrogen in the body will decrease. Estrogen is a hormone that can influence and help regulate body functions including the reproductive system, brain and central nervous system, bones, liver and urinary tract. Hormone replacement therapy (HRT) is intended to increase estrogen levels in postmenopausal women. One of the food ingredients that contain phytoestrogens and is widely consumed in Indonesia is tempe. The aim of the study was to make a tempe-based drink containing isoflavones (genestein, daidzein, glycetin) and nutrients (vitamin B3, vitamin B6, vitamin B12, folate) that are appropriate and sensory acceptable. The content of isoflavones and nutrients was analyzed using High Performance Liquid Chromatography (HPLC). Tempe flour which has been analyzed for its nutritional content and isoflavones, then a tempe drink formulation is made with isoflavones content, namely 15 milli grams (30 grams of tempe flour). To improve the flavor of the drink, add cocoa powder. The design used was a completely randomized design (CRD) with a single treatment, namely the concentration level of tempe flour for formula 1 (original tempe) = 17.5%, formula 2 (original tempe) = 14% and formula 3 (tempe with added chocolate as flavor). = 14 %. Acceptance of tempeh-based drinks was carried out by organoleptic tests in the form of hedogenic (liking) tests on 30 elderly women. In the first phase of the research that for color, taste, aroma and thickness the most preferred was the third formula with the addition of chocolate and 14% thickness. The conclusion is that tempe flour using the freeze dry method contains isoflavones and nutrients (vitamin B3, vitamin B6, vitamin B12 and folic acid) higher than tempe using the oven method but not significantly. Hedogenic test (favorability test) is the highest with a 14% viscosity formula and there is the addition of chocolate Keywords: tempe, elderly women, organoleptic test